View Single Post
May30-07, 07:01 PM
P: 3
Quote Quote by honestrosewater View Post
Did you try changing the implication to a disjunction first, before distributing the negation?

1] ~(p -> ~q)
2] ~(~p v ~q)
3] ?
Thanks for your reply honestrosewater.

Okay if I play that way

~(~p v ~q) <=> ~[~(p ^ q)] <=> p ^ q

Is that the correct process to acquire that answer then. First negate the antecedent and change the conditional to a disjunction. Then does the ~ distribute to both as in my answer above? Or am I going about this the wrong way?